Baznas’ integrated marketing communication strategy in building brand equity - Dadan Firdaus; Fauzan Jatnika Abror (Jurnal Iman dan Spiritualitas, 2026)
Indonesia boasts immense zakat potential—approximately IDR 327.6 trillion—yet realizes only 10% due to low literacy, eroded trust in official institutions, and entrenched informal practices via musollas, foundations, and direct aid to mustahik. This study examines how BAZNAS optimizes its IMC strategy to broaden reach, bolster trust, and foster muzakki loyalty to official channels. Employing a qualitative, descriptive-exploratory approach, it draws on purposive in-depth interviews, analyzed via thematic development, data reduction, and inference for recommendations. Findings reveal BAZNAS deploys three of eight IMC elements—product advertising, personal selling, public relations, and mobile marketing—anchored by the "Cahaya Zakat" umbrella message. Its brand equity stems from governmental authority, national coordination via provincial/district BAZDA networks, the 3A principles (Safe Syar'i, Safe Regulation, Safe NKRI), and personalized rituals like prayer recitation, sustaining muzakki commitment.